Cold Atmospheric Plasma Attenuates Breast Cancer Cell Growth Through Regulation of Cell Microenvironment Effectors - Aggelopoulos, Christos A.; Christodoulou, Anna-Maria; Tachliabouri, Myrsini; Meropoulis, Stauros; Christopoulou, Maria-Elpida; Karalis, Theodoros T.; Chatzopoulos, Athanasios; Skandalis, Spyros S. (Frontiers in Oncology, 2022)
Breast cancer exists in multiple subtypes some of which still lack a targeted and effective therapy. Cold atmospheric plasma (CAP) has been proposed as an emerging anti-cancer treatment modality. In this study, we investigated the effects of direct and indirect CAP treatment driven by the advantageous nanosecond pulsed discharge on breast cancer cells of different malignant phenotypes and estrogen receptor (ER) status, a major factor in the prognosis and therapeutic management of breast cancer. The main CAP reactive species in liquid (i.e. H2O2, NO2−/NO3−) and gas phase were determined as a function of plasma operational parameters (i.e. treatment time, pulse voltage and frequency), while pre-treatment with the ROS scavenger NAC revealed the impact of ROS in the treatment. CAP treatment induced intense phenotypic changes and apoptosis in both ER+ and ER- cells, which is associated with the mitochondrial pathway as evidenced by the increased Bax/Bcl-2 ratio and cleavage of PARP-1. Interestingly, CAP significantly reduced CD44 protein expression (a major cancer stem cell marker and matrix receptor), while differentially affected the expression of proteases and inflammatory mediators. Collectively, the findings of the present study suggest that CAP suppresses breast cancer cell growth and regulates several effectors of the tumor microenvironment and thus it could represent an efficient therapeutic approach for distinct breast cancer subtypes.